Private sector enabling policies for low-income housing delivery in Egypt - Sally Mahmoud Ali; Ahmed Mahmoud Yousry (Cairo : Sally Mahmoud Ali, 2013)
The research reviews the problem of low-income housing policies as one of the most crucial problems in Egypt. The Egyptian government has long adopted the housing provision policy, whereas many developed and developing countries have shifted to the private-sector enabling policy that involves investors in housing provision and allows them to lead the housing sector
Thesis (M.Sc.) - Cairo University - Faculty of Urban and Regional Planning - Department of Urban Design
Issued also as CD
Keywords: Enabling policies; Low; Private sector